The Accountancy Fresh Graduates of Wesleyan University – Philippines in the Light of the Skills Expectations of Industry Partners - Castillo, Manuel P.; Mamaclay, Ali G.; Adriano, Jose Arsenio R. (Advances in Social Sciences Research Journal, 2021)
Employers consider a graduate's achievements in the relevant discipline to be required but not sufficient for them to be hired. It is essential that we fully understand what future employers will accept and needed. In the past, a graduate degree would ensure the welfare of a student's future. Today, something more different. A mere college diploma is inadequate for an individual to secure a promising future. This study aims to determine the fresh graduates' professional accounting skills and technology skills needed by the company and demonstrated by the accounting graduates. Results of study analysis comprised twenty (20) companies showed that computing techniques, written communication, reporting skills, measurement skills, professionalism, and oral communication are what employers seek. Moreover, companies observed that accounting graduates are more knowledgeable in reporting, research, measurement, finance, strategic and critical thinking skills, and problem-solving skills. Regarding technology skills, companies seek employees knowledgeable in spreadsheet packages, accounting packages (SAP, Pastel, QuickBooks), word processing packages, communication software (Skype, Outlook, Slack), electronic commerce, and the worldwide web. However, accounting graduates possess word processing packages, communication software (skype, outlook, slack), world wide web, electronic commerce, and windows. It was revealed that students must be well-versed in Microsoft Office Applications, as this was the employers' primary skills needed both professional accounting skills and technology skills. These results provide the academicians with useful information. Building fundamentals, becoming competitive and continual development of abilities in accounting needs a tough knowledge foundation. Specializing in a specific area of accounting, such as financial reporting, taxation, or auditing, helps an individual become a highly sought-after professional. In a more distinct framework and profound lens, this study will convey collaborations on how Nueva Ecija industries search to hire new accounting professionals. In detail, the foregoing survey purposes were addressed: to determine the required skills the employers seek from accounting graduates, to identify the more important accountancy graduates' skills, to examine if do companies treat the professional accounting skills similar to technological skills, and to discover if there were any difference on the requirements of employers and the skills demonstrated by accounting graduates.